2017
DOI: 10.1111/ecc.12643
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of telephone support as perceived by patients with cancer: A systematic review

Abstract: Telephone‐based interventions can increase accessibility to healthcare and are increasingly used as a convenient method of providing support. We conducted a systematic review of published literature reporting adult patients’ perceptions of the acceptability of, and satisfaction with, telephone‐based interventions during or post‐treatment for cancer. Systematic searches identified 4,855 articles. Forty‐eight articles describing 50 studies were included in the review. Three intervention categories were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 73 publications
1
47
0
1
Order By: Relevance
“…A systematic review study addressed the acceptability of telephone support by cancer patients and concluded that this type of evidence related to patient perception is increasing. However, interpretation of the results is limited because of the instruments selected for the quantitative assessment of patient satisfaction, which do not always reflect patient-centered priorities emerging from qualitative data (11) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review study addressed the acceptability of telephone support by cancer patients and concluded that this type of evidence related to patient perception is increasing. However, interpretation of the results is limited because of the instruments selected for the quantitative assessment of patient satisfaction, which do not always reflect patient-centered priorities emerging from qualitative data (11) .…”
Section: Discussionmentioning
confidence: 99%
“…Its main intervening factors are concern with the reduction of healthcare costs, epidemiological factors and geographical barriers (10) . Fixed or mobile phones are used by most of the population, increasing the individuals' access to healthcare, and have proven to be a convenient method to support healthcare services (11) . According to the Nursing Interventions Classification (NIC), telephone follow-up is defined as providing results or evaluating a patient's response and determining potential for problems as a result of previous treatment, examination or testing, over the telephone (12) .…”
Section: Introductionmentioning
confidence: 99%
“…While adjusting AEDs on telemedicine, the side-effect of AEDs should be considered. Telemedicine allows us to weigh the side-effects of the treatment ( 17 ). In case of critical side-effects, clinicians may consider physical consultation.…”
Section: Decision Making On Telemedicinementioning
confidence: 99%
“…Internet delivered cognitive behavioural therapy (iCBT) is an effective way to treat psychiatric and somatic conditions in children and adolescents (Vigerland et al, 2016[66]) and improve sleep in adults with insomnia (Seyffert et al, 2016[70]). Furthermore, it is as effective as usual care in reducing symptoms of depression (Deady et al, 2017[73]; van Beugen et al, 2014 [74]; Linde et al, 2015 [75]). mHealth can reduce symptoms of anxiety, stress and depression while improving patient adherence and reducing face-to-face visits (Rathbone and Prescott, 2017 [71]).…”
mentioning
confidence: 99%
“…Telemedicine is at least as effective as usual approaches to nutrition and physical activity. Telemedicine interventions are comparable to face-to-face interventions in improving physical activity and reducing sedentary behaviour (Direito et al, 2017 [74]), while targeted interventions are more effective than usual care in increasing physical activity (Hakala et al, 2017[75]). Telemedicine interventions can improve diet quality, including the intake of fruits, vegetables, and dietary sodium for people with chronic conditions (Kelly et al, 2016 [76]) and for malnourished community dwelling older adults (Marx et al, 2018[83]).…”
mentioning
confidence: 99%